CIVIL SERVICE CANDIDATE TRUST IN GOVERNMENT PERFORMANCE IN IMPLEMENTATION OVERCOMING CORONA VIRUS POLICY IN TANAH LAUT REGENCY - Bornea Retno Mahalayati; M. Noveriyadie; Hanil Sadikin; Muzahid Akbar Hayat (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2020)
The purpose of this policy communication study was to determine the effect of Mata Najwa's impressions on September 28, 2020, on 17 respondents of CPNS Formation 2019 in Tanah Laut Regency. The focus of the research was determined on the influence of Mata Najwa on the trust of 17 respondents of the 2019 CPNS Formation in Tanah Laut Regency on the performance of the government in dealing with the Corona Virus using the Hypodermic Needle Theory, this theory includes Cognitive Effects, Affective Effects, Behavioral Effects. Policy communication study is a qualitative descriptive study. Data collection was carried out by interview, questionnaire, observation, and documentation. The results of research on 17 2019 CPNS Formation Respondents in Tanah Laut Regency show that there are passive audiences who in different situations can become active audiences. All informants get cognitive effects and affective effects, but on behavioral effects, not all informants experience these effects, but only slightly.